Pomegranate juice (Punica granatum) as an ideal mouthrinse for fixed orthodontic patients - Haryono Utomo; Kimberly Clarissa Oetomo (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Prevention of caries as well as periodontal disease is mandatory during orthodontic treatment. Nevertheless, the use of antiseptic mouthrinse is contraindicated for prolonged use. Pomegranate juice is a polyphenol-rich juice with high antioxidant capacity as well as antimicrobial properties. It has been shown to exert beneficial characteristics for orthodontic patients such as antioxidant and anti inflammatory effects. Moreover, it contained fluoride and phosphorous which are cariostatic. Previous study in fixed orthodontic patients revealed that rinsing with this juice showed reduced dental plaque and superior compared with chlorhexidine. If it has unwanted effect by reducing pro-inflammatory reaction that also needed in orthodontic movement is not clearly understood. Purpose: The aim of the present review was to discuss the beneficial and unwanted effect of pomegranate juice mouthrinse towards orthodontic treatment. Reviews: Pomegranate has antimicrobial activity, its methanolic skin extract is the most potent followed by seed juice. Nevertheless, seed juice is not only tastier, easier to make but also has mild antimicrobial potency which is beneficial for long-term use. Healthy periodontal tissue is preferable for orthodontic movement since it resulted in less unwanted bone resorption. Conclusion: Regarding its beneficial effect and safety of pomegranate juice if use daily mouthrinse in fixed orthodontic patients, it could be proposed as an ideal long term use mouthrinse for fixed orthodontic patients. However, further researches should be done to verify this concept.Latar belakang: Pencegahan karies dan penyakit periodontal sangat penting dalam perawatan ortodontik. Walaupun demikian, penggunaan obat kumur antiseptik jangka panjang merupakan kontraindikasi. Jus buah delima sangat kaya akan polifenol dengan kemampuan antioksidan yang tinggi disertai kemampuan antimikroba. Beberapa penelitian telah menunjukkan dampak menguntungkan pada pasien ortodonti, yaitu sebagai antioksidan dan anti radang. Selain itu juga mengandung fluor dan fosfor yang bersifat kariostatik. Penelitian terdahulu pada pasien ortodonti cekat menunjukkan penurunan plak gigi yang lebih banyak dibanding dengan klorheksidin. Akan tetapi, apakah juga menyebabkan dampak merugikan yaitu mengurangi reaksi keradangan yang juga penting bagi pergerakan ortodonti masih belum jelas. Tujuan: Membahas dampak menguntungkan maupun merugikan jus buah delima pada perawatan ortodonti. Tinjauan pustaka: Buah delima merupakan antimikroba, ekstrak dari kulit yang mengandung metanol adalah paling kuat diikuti jus biji delima. Akan tetapi, jus biji lebih enak rasanya, mudah dibuat dan merupakan antimikroba ringan sehingga menguntungkan untuk pemakaian jangka panjang. Jaringan periodontal yang sehat diperlukan untuk pergerakan ortodonti karena dapat mengurangi resorpsi tulang. Kesimpulan: Berdasarkan dampak menguntungkan dan keamanan jus buah delima bila digunakan tiap hari, bahan ini dapat diusulkan sebagai obat kumur jangka panjang yang ideal untuk pasien ortodonti cekat. Walaupun begitu, penelitian lebih lanjut harus dilakukan untuk verifikasi konsep ini.